Effects of web-based instruction and patient preferences on patient-reported outcomes and learning for women with advanced ovarian cancer: A randomized controlled trial. Issue 4 (4th July 2018) - Petzel, Sue V.; Isaksson Vogel, Rachel; Cragg, Julie; McClellan, Molly; Chan, Daniel; Jacko, Julie A.; Sainfort, François; Geller, Melissa A.
ABSTRACT: A randomized controlled trial was conducted of a web-based intervention to improve advanced care planning in women with ovarian cancer. A secondary analysis of 35 randomized women focused on changes in distress and knowledge about ovarian cancer through distress monitoring and information tailored to patients' cognitive coping style (monitoring, blunting). Pre-/postresults indicated the Intervention group demonstrated lower distress ( p = 0.06); blunting was associated with lower depression ( p = 0.04); knowledge in both groups was unchanged. Women in the Intervention vs. Control group reported their family was less likely to be upset by cancer information ( p = 0.0004). This intervention reduced distress while incorporating patient preferences.